Adaptive algorithms for change point detection in financial time series - Alexander Musaev; Dmitry Grigoriev; Maxim Kolosov (AIMS Mathematics)
The detection of change points in chaotic and non-stationary time series presents a critical challenge for numerous practical applications, particularly in fields such as finance, climatology, and engineering. Traditional statistical methods, grounded in stationary models, are often ill-suited to capture the dynamics of processes governed by stochastic chaos. This paper explores modern approaches to change point detection, focusing on multivariate regression analysis and machine learning techniques. We demonstrate the limitations of conventional models and propose hybrid methods that leverage long-term correlations and metric-based learning to improve detection accuracy. Our study presents comparative analyses of existing early detection techniques and introduces advanced algorithms tailored to non-stationary environments, including online and offline segmentation strategies. By applying these methods to financial market data, particularly in monitoring currency pairs like EUR/USD, we illustrate how dynamic filtering and multiregression analysis can significantly enhance the identification of change points. The results underscore the importance of adapting detection models to the specific characteristics of chaotic data, offering practical solutions for improving decision-making in complex systems. Key findings reveal that while no universal solution exists for detecting change points in chaotic time series, integrating machine learning and multivariate approaches allows for more robust and adaptive forecasting models. The work highlights the potential for future advancements in neural network applications and multi-expert decision systems, further enhancing predictive accuracy in volatile environments.